Ask a New Question
Search
Questions and answers by
iza m.
Answers (3)
hi! in order to solve this you will need to incorporate a bit of algebra. first off, you have to produce the equations for each reactions. NaCl + AgNO3 ---> AgCl + NaNO3 KCl + AgNO3 ---> AgCl + NaNO3 and let NaCl = x ; KCl = y since the sample is equal to
hi! in order to solve this you will need to incorporate a bit of algebra. first off, you have to produce the equations for each reactions. NaCl + AgNO3 ---> AgCl + NaNO3 KCl + AgNO3 ---> AgCl + NaNO3 and let NaCl = x ; KCl = y since the sample is equal to
hi! in order to solve this you will need to incorporate a bit of algebra. first off, you have to produce the equations for each reactions. NaCl + AgNO3 ---> AgCl + NaNO3 KCl + AgNO3 ---> AgCl + NaNO3 and let NaCl = x ; KCl = y since the sample is equal to